Vasily Dvortsov’s “Cain’s Kin” a novel not only about theatre - Małek, Eliza (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The subject of the present investigation is the novel by a contemporary author Vasily Dvortsov, enigmatically titled ‘Kainovo koleno’ (‘Cain’s Kin’). In the article it is shown how the writer projects the biblical story of Cain’s descendants onto the contemporary life in the Soviet Union and the new Russia, thereby depicting the spiritual and moral crisis of the Russian intelligentsia, first of all in the theatre milieu. The writer sees the causes of the spiritual and professional degradation of his protagonist, Sergei Rozanov, in the latter’s pursuit of worldly fame and in his non-observance of God’s commandments.